Four new species and further records of Dorvilleidae (Annelida, Polychaeta) from deep-sea organic substrata, NE Atlantic - Ravara, Ascensão; Wiklund, Helena; Cunha, Marina R. (European Journal of Taxonomy, 2021)
Eight species of Ophryotrocha and one of Parougia were identified from organic substrata (wood and alfalfa) sampled at the Gulf of Cadiz and Western Iberian Margin (NE Atlantic). Morphological examination and molecular phylogenetic analyses, based on the nuclear gene H3 and the mitochondrial gene 16S, indicate the presence of four species new to science: Ophryotrocha chemecoli sp. nov., O. nunezi sp. nov., O. geoffreadi sp. nov. and Parougia ougi sp. nov. The geographic and/or bathymetric distribution is extended for four previously known species: O. cantabrica, O. hartmanni, O. mammillata and O. scutellus. Another species may also have its distribution extended, pending the molecular confirmation of its identity: O. lipscombae. Full descriptions and figures are given for all the new species and, when justified, also for the previously known ones. The original description of O. scutellus is amended. New DNA sequences are given for eight of the nine species studied here. The ecology and geographic distribution of the reported species is discussed.